2020
DOI: 10.21037/gs.2020.03.41
|View full text |Cite
|
Sign up to set email alerts
|

Lymphaticovenular anastomosis for breast cancer-related upper extremity lymphedema: a literature review

Abstract: Breast cancer-related lymphedema is a long-term condition that affects almost half of breast cancer survivors. Clinical studies have looked at the benefits of lymphaticovenular anastomosis (LVA) for the treatment of upper extremities lymphedema after breast cancer, however, there is still controversy if it improves lymphedema. This study aimed to analyze the studies and outcomes related to LVA for breast cancer-related lymphedema. A PubMed/Medline search was performed using "lymphovenous bypass", "upper extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Most studies reported a reduction in volume or circumference measurement after surgery, even though there were various techniques for objective assessment. 67,68 The effectiveness of LVA is also proven by Salgarello et al 69 In their study, a decreasing episode of lymphangitis and reduction in the number of physiotherapy sessions, as well as compressive class garment, could be achieved after LVA.…”
Section: Discussionmentioning
confidence: 73%
“…Most studies reported a reduction in volume or circumference measurement after surgery, even though there were various techniques for objective assessment. 67,68 The effectiveness of LVA is also proven by Salgarello et al 69 In their study, a decreasing episode of lymphangitis and reduction in the number of physiotherapy sessions, as well as compressive class garment, could be achieved after LVA.…”
Section: Discussionmentioning
confidence: 73%
“…Second, LYMPHA is performed mostly by plastic surgeons trained in microsurgery. Despite the prevalence of breast cancer surgery nationwide, LYMPHA technique is not standardized 18 and not all institutions are equipped to provide these specialized procedures. Furthermore, greater coordination efforts and referral patterns would be needed between breast and plastic surgeons to enable prophylactic surgery at the time of mastectomy because nearly 85% of breast surgeons reported not offering LYMPHA in a recent survey study 19 .…”
Section: Funding Supportmentioning
confidence: 99%
“…It is also essential in preventing recurrence and complications such as skin infections, ulcers, and lymphatic leakage (Ozcan et al, 2018). Additionally, major advancements in super‐microsurgery have driven the development of a broader interest among surgeons in the pursuit of a decisive surgical algorithm for the treatment of lymphedema (Ciudad, Manrique, Bustos, Coca, et al, 2020; Escandón et al, 2022; Forte et al, 2020; Kung et al, 2017; Nicoli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%